2016
DOI: 10.1007/s00775-016-1357-8
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and binuclear non-heme iron chemistry from a theoretical perspective

Abstract: In this minireview, we provide an account of the current state-of-the-art developments in the area of mono-and binuclear non-heme enzymes (NHFe and NHFe2) and the smaller NHFe(2) synthetic models, mostly from a theoretical and computational perspective. The sheer complexity, and at the same time the beauty, of the NHFe(2) world represent a challenge for both experimental as well as theoretical methods. We emphasize that the concerted progress on both theoretical and experimental side is a conditio sine qua non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 239 publications
1
21
0
Order By: Relevance
“…The details of the O 2 activation/decarboxylation steps are very sensitive to the choice of method and model, and their full elucidation may require further developments, especially in the area of multi-reference methods capable of treating larger systems. 9,87 However, in the meantime, the present conclusions appear sufficiently robust to inform further computational and experimental efforts aimed at uncovering the factors that control the unique reactivity and selectivity of SyrB2 and related NHFe halogenases.…”
Section: Discussionsupporting
confidence: 53%
“…The details of the O 2 activation/decarboxylation steps are very sensitive to the choice of method and model, and their full elucidation may require further developments, especially in the area of multi-reference methods capable of treating larger systems. 9,87 However, in the meantime, the present conclusions appear sufficiently robust to inform further computational and experimental efforts aimed at uncovering the factors that control the unique reactivity and selectivity of SyrB2 and related NHFe halogenases.…”
Section: Discussionsupporting
confidence: 53%
“…H ydrogen atom abstraction (HAA) is a seemingly simple process, in which an electron and proton pair is concomitantly transferred from a substrate to an oxidant (or to an oxidant/base pair) (1). One example is C-H bond homolysis by a strong oxidant, which is the rate-determining step in many chemical transformations (2,3) and the modus operandi of many metalloenzymes in substrate activation (4). A growing body of experimental and theoretical studies dedicated to HAA chemistry has revealed its fascinating complexity (5), which concerns, among other things, (i) a distinction between proton-coupled electron-transfer (PCET) and hydrogen atom transfer (HAT) mechanisms (6-10); (ii) tunneling contributions to reactivity, as reflected by large H/D kinetic isotope effects (KIEs) and their dependence on temperature (11)(12)(13); and lastly (iii) a wellrecognized linear/quadratic relationship (9,14,15) between the free energy of activation (ΔG ≠ ) and the free energy of reaction (ΔG 0 ).…”
mentioning
confidence: 99%
“…This was followed very recently by including DMRG (DMRG-PDFT). [144] 3.4 Methods put to the test: recent benchmark studies Over the years, many studies [145,70,146,147,31,148,149,111,85,67,68,65,[150][151][152][153][154][155]112,[156][157][158][159] have been reported on spin-state splittings for a wide variety of transition-metals, in different oxidation states, using a variety of DFAs and wavefunction methods. One of the motivations for the ECOSTBio COST Action CM1305 [160] was indeed to gather experts from different areas of chemical research and move forward in the search for consensus on transition-metal chemistry, and which computational and experimental methods could be used for getting accurate descriptions of the geometry, electronic structure and spectroscopy of transitionmetal complexes.…”
Section: Combining Wavefunctions and Density Functionals: Mc-pdft And Dmrg-pdftmentioning
confidence: 99%